CREATING GRAPHIC DESIGN AS A BRANDING MEDIUM FOR THE CULTURAL EVENT PASAR DUGDERAN SEMARANG - Maulana, Ardilla; Haryanto, Eko (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Pasar Dugderan is one of Semarang's annual cultural events, not only serving as a commemoration of the month of Ramadan but also as a symbol of Indonesian culture that upholds historical, social, and spiritual values. Indonesia is a country rich in culture and language, making cultural events such as Dugderan play an important role in strengthening national identity and preserving culture and traditions amidst the current of modernization. The author designed a graphic design that highlights typical Dugderan elements such as Warak Ngendhog, traditional ornaments, and local patterns that represent the nuances of Semarang's local culture and Javanese culture more broadly. This design includes visual exploration, color selection, typography, and the application of design to promotional and branding media such as posters, banners, and social media. The goal of this design is to create a visual identity that is not only communicative and aesthetic, but also able to depict the spirit of Indonesia's cultural diversity in an attractive package, especially for the younger generation. The final result of this design is expected to make a positive contribution to efforts regarding the preservation of local culture and to increase awareness of the importance of national cultural heritage in the era of globalization.